Raising Public Awareness of Air Pollution and How to Mitigate The Health Risk - Endah Saptutyningsih; Berli Paripurna Kamiel (Universitas Muhammadiyah Surakarta, 2021)
This Community Partnership Program (PKM) aims to increase public awareness about the negative impacts of air pollution and how to mitigate it. This PKM handing over air pollution monitoring tools, counseling, and planting air pollution reducing plants. The results of this community partnership is the presence of counseling can increase understanding of the negative impacts of air pollution. Public awareness to mitigate the negative impact of air pollution has increased after attending the counseling. As for the mitigation that will be carried out by the community, including planting air pollution reducing plants, routine motor vehicle servicing and reducing the use of motorized vehicles. The community service program is based on the results of air pollution mapping in the city of Yogyakarta. Programs to raise public awareness about health risks due to air pollution are still rare in Yogyakarta and the importance of knowledge about ways to mitigate air pollution risks.